Chances and risks of a European unemployment benefit scheme - Dolls, Mathias (Mannheim, 2016)
"The Eurozone debt crisis has revived the debate about deeper fiscal integration in the European Economic and Monetary Union (EMU). Some observers argue that fiscal risk sharing is necessary to make the Eurozone more resilient to macroeconomic shocks and to avoid its break-up. However, the main concerns relate to the issues of permanent transfers across Member States and moral hazard. The 2012 Four Presidents’ Report suggested that fiscal integration could include a common unemployment insurance system. A White Paper outlining further steps necessary to complete EMU is to be released by the European Commission in the spring of 2017. This ZEW policy brief presents new research findings on the stabilizing and redistributive effects of a common unemployment insurance scheme for the euro area (henceforth EMU-UI).1 It provides insights regarding its potential added value and discusses moral hazard issues."